Measuring the Electrical Status of the Bionic Ear. Re-thinking the Impedance in Cochlear Implants - Di Lella, Federico A.; Parreño, Matias; Fernandez, Florencia; Boccio, Carlos M.; Ausili, Sebastián A. (Frontiers in Bioengineering and Biotechnology, 2020)
As in any biophysical electrode-tissue environment, impedance measurement shows a complex relationship which reflects the electrical characteristics of the medium. In cochlear implants (CIs), which is mostly a stimulation-oriented device, the actual clinical approach only considers one arbitrary time-measure of the impedance. However, to determine the main electrical properties of the cochlear medium, the overall impedance and its subcomponents (i.e., access resistance and polarization impedance) should be described. We here characterized, validated and discussed a novel method to calculate impedance subcomponents based on CI measurement capabilities. With an electronic circuit of the cochlear electrode-tissue interface and its computational simulation, the access resistance and polarization impedance were modelled. Values of each electrical component were estimated through a custom-made pulse delivery routine and the acquisition of multiple data points. Using CI hardware, results fell within the electronic components nominal errors (±10%). Considering the method’s accuracy and reliability, it is readily available to be applied in research-clinical use. In the man-machine nature of the CI, this represents the basis to optimize the communication between a CI electrode and the spiral ganglion cells.